Atypical Femoral Fracture in Osteoporosis Pseudoglioma Syndrome Associated with Two Novel Compound Heterozygous Mutations in LRP5. (April 2015) - Alonso, Nerea; Soares, Dinesh C; V McCloskey, Eugene; Summers, Gregory D; Ralston, Stuart H; Gregson, Celia L
ABSTRACT: Osteoporosis pseudoglioma syndrome (OPPG) is a rare autosomal recessive condition of congenital blindness and severe childhood osteoporosis with skeletal fragility, caused by loss‐of‐function mutations in the low‐density lipoprotein receptor‐related protein 5 ( LRP5 ) gene. We report the first case of atypical (subtrochanteric) femoral fracture (AFF) in OPPG, occurring in a 38‐year‐old man within the context of relatively low bone turnover and trabecular osteoporosis on bone histology. We identify two novel LRP5 mutations: R752W is associated with low bone mineral density (BMD), as demonstrated by the heterozygous carriage identified in his 57‐year‐old mother; however, the combination of this R752W mutation with another novel W79R mutation, causes a severe case of compound heterozygous OPPG. We undertake 3D homology modeling of the four extracellular YWTD β‐propeller/EGF‐like domains (E1–E4) of LRP5, and show that both novel mutations destabilize the β‐propeller domains that are critical for protein and ligand binding to regulate Wnt signaling and osteoblast function. Although AFFs have been reported in other rare bone diseases, this is the first in a genetic condition of primary osteoblast dysfunction. The relatively low bone turnover observed, and knowledge of LRP5 function, implicates impaired bone remodeling in the pathogenesis of AFF. © 2014 American Society for Bone and Mineral Research © 2014 American Society for Bone and Mineral Research.